Stem Cells Therapy for COVID-19: A Systematic Review and Meta-Analysis - Arabpour, Erfan; Khoshdel, Sina; Tabatabaie, Negin; Akhgarzad, Ali; Zangiabadian, Moein; Nasiri, Mohammad Javad (Frontiers in Medicine, 2021)
Introduction: Since its primary detection on December 2019 in China,COVID-19 have been caused more than 175 million infected cases and 3.7 million deaths up to 10 June 2021.Vaccination seems to be a good solution for this pandemic but because of vaccination challenges,there are still people who get the disease.So investigating new therapies for COVID-19 is necessary.The aim of this study is to evaluate the safety and efficacy of one of COVID-19 therapeutic options;mesenchymal stem cells. Methods: A meta-analysis was performed using pubmed,embase,scopus, clinicaltrials.gov,google scholar and L·OVE.The risk ratio(RR) and associated 95% confidence intervals(CI) were obtained.Datas were analyzed by “Comprehensive Meta-Analysis” software,Version 2.0 (Biostat,Englewood,NJ). Results: Of the 1262 identified articles,finally 10 articles approved to be included. 9 studies were included in the meta-analysis.The analysis showed MSC therapy could significantly reduce mortality (RR 0.471,95% CI 0.270-0.821) and morbidity (RR 0.788,95% CI 0.626-0.992) rate in COVID-19 patients;compared to the control group.Also the systematic review of 10 articles showed that MSCs are safe to use and can improve pulmonary function and ameliorate symptoms due to immunomodulatory effects. Conclusion: The present study suggest that MSC therapy has a remarkable effect on treatment of COVID-19 infection.Further large-scale studies needed to approve these results.Defining a protocol for MSC therapy in COVID-19 patients can leadvto achieve the best clinical outcomes.